2023
DOI: 10.3390/su15042963
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Credit Accessibility of Rice Farmers in Pakistan: Analysis for Central Punjab and Khyber Pakhtunkhwa Regions

Abstract: This study investigates the factors that affect farmers’ access to Food Security and Agricultural Credit (FSAC) services for the farmers of Pakistan who have no access to banking but have a feasible farm business. Using multiple regressions and logistic analysis, the authors revealed the determinants of farmers’ financial literacy and analyzed the variables which affected the farmers’ accessibility to FSAC. Results indicated that the average financial literacy of respondents was at a moderate level. It was aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A close-ended structured questionnaire was used for data collection. In earlier studies in the region, Asdullah and Yazdifar [64], Anjum and Ming [65], Pathan et al [66], and Raza et al [45] demonstrated that it was easier for respondents to comprehend and reply to close-ended questions compared to open-ended ones. As the population under study comprises farmers, who have lower literacy and knowledge, it is better to select the easier questionnaire style.…”
Section: Research Design Sampling and Data Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…A close-ended structured questionnaire was used for data collection. In earlier studies in the region, Asdullah and Yazdifar [64], Anjum and Ming [65], Pathan et al [66], and Raza et al [45] demonstrated that it was easier for respondents to comprehend and reply to close-ended questions compared to open-ended ones. As the population under study comprises farmers, who have lower literacy and knowledge, it is better to select the easier questionnaire style.…”
Section: Research Design Sampling and Data Collectionmentioning
confidence: 98%
“…Financial inclusion has several benefits, including access to credit, improved opportunities for savings, and improved financial literacy [26,44]. Financial inclusion also aids in poverty reduction and inequality and promotes economic growth [45]. Financial inclusion leads to the provision of increased access to financial services for individuals and communities that have been ignored in the past, leading to the creation of opportunities for poverty reduction.…”
Section: Financial Inclusion and Sustainable Farm Performancementioning
confidence: 99%
“…Individuals' desire to become entrepreneurs can be influenced by various personal circumstances (Murugesan & Dominic, 2013). The majority of scholars held the opinion that saving and financial literacy have a direct or indirect impact on people's desire to start their own business and entrepreneurial intent (Hilgert et al, 2003;Li & Qian, 2020;Rikwentishe et al, 2015) A person's financial welfare and security depend heavily on their financial literacy (Raza et al, 2023). Numerous scholars have demonstrated that people with a high degree of financial literacy can readily acquire the skills required for risk management, recognize business possibilities, and learn about markets and finance to support the expansion of venture formation and entrepreneurship (Klapper et al, 2015;Li & Qian, 2020).…”
Section: H2: Financial Behavior Has a Significant And Positive Effect...mentioning
confidence: 99%
“…The larger the collection of elements related to information acquisition, communication, and utilization, the more ways for farmers to collect information and acquire more financial knowledge. As financial literacy improves, farmers are likely to be more willing to obtain formal financial loans, and less likely to hide personal information due to conservatism, hence effectively mining farmer's credit information and reducing the information barriers between banks and farmers (Raza et al, 2023).…”
Section: Theoretical Logic Analysis Of Accelerating Savings To Invest...mentioning
confidence: 99%